Lucifer. Blood in the streets / Volume 3, - Black, Holly; Kadrey, Richard (Lucifer, 2017)
"After his harrowing confrontation with God himself, it's time for Lucifer to enjoy the season to be merry. Featuring a Krampus-approved holiday special, this third volume of the new hit LUCIFER series takes the bringer of light through the streets of Los Angeles, the depths of the underworld and the deepest recesses of his own mind while he tries to live his life as a part of an ancient evil tradition and as a member of the living world."--